(untitled) (Journal of Governance and Development (JGD), 2015)
Social business is an investment purely for the purpose of achieving social objectives with no personal gains by the investors. The concept is being directly or indirectly adopted by a growing number of government agencies and non-profit organizations globally. The approach is adopted due to its power to promote social and economic changes to the society. In Malaysia contact a few agencies are running social business to increase economic equity among the society including Amanah Ikhtiar Malaysia (AIM). AIM has been well-known with so many success stories in turning the poor into successful entrepreneurs. It is believed that amongst the reason of the success because AIM exploits a unique approach, dissimilar to other conventional credit agencies in Malaysia in disbursing its microcredit facilities to the borrowers. The purpose of this paper is to compare theoretical framework outlined as social business by the Grameen Creative Lab with the objectives, strategies, values and practices embraced by AIM and to discover the critical success factors that have contributed to the organization’s present accomplishment as a social business organization. To achieve the objective of this paper, a theoretical framework of principles/ standard outlined as social business by Grameen Creative Lab is used for the comparison purposes. The criteria/factors in the framework are compared with AIM’s process of selecting the borrowers, the method of loan disbursement and repayment and other activities, strategies, services and amenities provided by AIM to the borrowers. Qualitative data collection, specifically semi-structured interview approach is used to obtain data from AIM. The findings indicate that there is a gap exists between the perceived strategy of social business and AIM’s strategy and approaches to achieve its main objective that is to alleviate poverty. The study also discovers that there are certain special personal qualities nurtured amongst AIM’s staff and borrowers that able to foster continued success of large number borrowers’ entrepreneurship projects. These personal qualities have critically contributed to AIM’s present accomplishment.